Late-onset systemic lupus erythematosus in the elderly - N. G. Klyukvina (Современная ревматология, 2018)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with various organs and systems involved in the pathological process. There is strong evidence that age at disease onset may influence the clinical presentations and prognosis of SLE. The paper analyzes the clinical and laboratory features of onset of SLE after the age of 50 years and possible reasons for differences in the manifestations of the disease in relation to racial and genetic factors. It considers the problems of differential diagnosis. There are data available in the literature and the results of the author's own investigations.